نشاط الشخصيات الجزائرية المهاجرة إلى فرنسا وتأثيره في الثورة التحريرية 1954 ـ 1962 - عمراوي ليندة (البليدة2- كلية العلوم الإنسانية و الإجتماعية, 2025)
إن التطرّق لتاريخ الثورة التحريرية على الأراضي الفرنسية يفرض علينا الحديث عن رموز ساهمت بشكل أو بآخر في نجاح مسيرة النضال الثوري للمهاجرين الجزائريين في أوروبا عامة وفي فرنسا بشكل خاص، وإسهاماتهم البالغة في معركة تحرير البلاد من ويلات احتلال غاشم دام أزيد من 100سنة، ارتكب خلالها ما لا يتخيّله عقل، ولا يصدّقه منطق، ولا يتحمّله بشر. شكّلت الشخصيات الجزائرية المهاجرة بفرنسا سواء التي نشطت سياسيا أو عسكريا أو حتى في مجالات أخرى، مصدر دعم كبير للقضية الوطنية وللثورة التحريرية ماديا وبشريا، ومصدر خطر عظيم وتهديد مباشر للسلطات الفرنسية في عقر دارها، ومنطلقا حقيقيا لكسب تأييد الرأي العام العالمي وتدويل المسألة الجزائرية، حيث نجحت في تجنيد القوى الوطنية بالمهجر لصالح الكفاح الثوري، ودفعها للإسهام في إنجاحه ماديا ومعنويا، فشكلوّا بذلك ملحمة نضال حقيقية ودفعا قويا للثورة خارج حدودها الإقليمية، ومصدر فخر وإلهام للأجيال الحالية والمستقبلية. لقد آمن هؤلاء الرجال بقضية وطنهم وأقسموا أن يعيشوا فوق الأرض أحرارً وأعزّاءً أو يموتون ويُدفنون تحتها شهداءً، وهذا ما كان لهم في النهاية حيث نال الكثير منهم شرف الشهادة في سبيل الله والوطن، في حين عاش بعضهم في أحضان الحرية والاستقلال وحقّقوا حلم حياتهم بتحرير بلادهم من براثن الاستعمار، وشكّلوا بذلك رموزا وطنية فاعلة ارتبط اسمها بتاريخ فدرالية جبهة التحرير الوطني والثورة التحريرية بفرنسا. Analyzing the history of the liberation revolution in France requires a review of those individuals that played a role in assisting the revolutionary struggle of Algerian immigrants in Europe—primarily in France—and the significant role they had in the struggle to release the country from a savage occupation that lasted more than one century. In that time, things took place that no one could imagine—things that no reasoned argument could justify, and things that were difficult to bear. Algerian expatriate communities in France, whether politically, military, or otherwise engaged, represented a fundamental source of material and human support for the national cause and liberation revolution. Because they also constituted a strategic threat to French authorities directly at their doorstep, they were vital for the French state to contain. Likewise, they enabled and facilitated a critical site for international solidarity and globalizing the Algerian question. Their monumental ability to mobilize nationalist forces abroad to act in support of the revolutionary struggle - both financial and moral - created a true epic of resistance. In the process, the Algerian expatriate community became a true extension of the revolution into the world beyond Algeria, establishing a legacy of pride and inspiration for all present and future generations in Algeria. These men fully embraced their country's cause, pledging to exist as free and honorable men, or to die and be buried as martyrs of this land. Ultimately, many achieved the status of martyrs under God's name and his nation, while others lived and revelled in freedom and independence, fulfilling what was the dream of a lifetime for all those who lived to free their own country from colonial rule. Thus, they have become lasting national symbols, whose names will always be linked to the FLN history and the liberation revolution in France
تخصص المهاجرون المغاربة بفرنسا ودورهم الوطني والقومي1962 – 1871
Keywords: المهاجرين الجزائريين بفرنسا; فدرالية جبهة التحرير الوطني; الكفاح الثوري; النضال السياسي; الفئات الطلابية المهاجرة